2022
DOI: 10.3389/fmars.2022.1001942
|View full text |Cite
|
Sign up to set email alerts
|

Gracilaria gracilis and Nannochloropsis oceanica, singly or in combination, in diets alter the intestinal microbiota of European seabass (Dicentrarchus labrax)

Abstract: Algae feeds and fish gut microbiota have been given importance in the past few years because of the necessity to rely on sustainable ingredients in aquafeeds and the link of host-associated microbes to organismal health. But little is known about the potential of algae, particularly of micro- and macroalgae combination, to shape the intestinal bacterial communities. Hence, in the present work, the 16S rRNA gene sequencing technique was employed to unravel the effects of the seaweed Gracilaria gracilis and the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 96 publications
1
3
0
Order By: Relevance
“…However, a clear difference at the phylum level was noted by the abundance of Actinomycetota and Parcubacteria in the blood microbiome, but not in the mucus, of both migratory and sedentary trout. This signature is, in fact, similar to a recent metagenomic study showing that bacteria enriched in seawater in polar regions were mostly Pseudomonadota, Actinomycetota, Bacteroidota, and Parcubacteria [50], the latter being one of the most abundant phyla in intestinal fish microbiota [57,58]. Interestingly, we also found a similar signature in the hemolymphatic (blood-like) microbiome of mussel species (Figure S10) that inhabit the coastal marine ecosystems of the Kerguelen Islands [59].…”
Section: Discussionsupporting
confidence: 89%
“…However, a clear difference at the phylum level was noted by the abundance of Actinomycetota and Parcubacteria in the blood microbiome, but not in the mucus, of both migratory and sedentary trout. This signature is, in fact, similar to a recent metagenomic study showing that bacteria enriched in seawater in polar regions were mostly Pseudomonadota, Actinomycetota, Bacteroidota, and Parcubacteria [50], the latter being one of the most abundant phyla in intestinal fish microbiota [57,58]. Interestingly, we also found a similar signature in the hemolymphatic (blood-like) microbiome of mussel species (Figure S10) that inhabit the coastal marine ecosystems of the Kerguelen Islands [59].…”
Section: Discussionsupporting
confidence: 89%
“…On the contrary, a high inclusion (8%) of G. gracilis resulted in a significant reduction of gut microbial diversity. However, these negative impacts were mitigated at a lower inclusion level (4%) [197]. Tapia-paniagua et al [198] reported that a relatively low (<3%) dietary administration of Ulva ohnoi significantly enhanced the diversity of whole gut microbes in Senegalese sole (Solea senegalensis), while 5% U. ohnoi did not exhibit a significant influence on gut microbial diversity [196].…”
Section: Gut Microbiota Compositionmentioning
confidence: 99%
“…Seaweed has been shown to be a promising feed additive that can modulate the gut microbial composition of fish [196]. The dietary inclusion of Gracilaria gracilis enhanced the abundance of the microbes Sulfitobacter and Methylobacterium in the gut of European seabass [197]. These microbes are capable of producing short-and medium-chain fatty acids and can lower the pH of the intestine, thus playing a crucial role in suppressing pathogenic bacteria and potentially representing a promising method of enhancing disease resistance in fish [213,214].…”
Section: Gut Microbiota Compositionmentioning
confidence: 99%
“…This analysis reported that the anterior and mid sections are mostly associated with feed digestion and nutrient absorption, whereas the posterior/rectal segments are especially relevant for immune functions 26 . The posterior/rectal regions are also the preferred sections for understanding the diet-induced modulation of the microbial communities 27 30 . Nonetheless, the lack of a comprehensive study of the morphology and physiology of seabass intestine hampers the ability to selectively modulate specific targeted traits and hence contribute to precision nutrition.…”
Section: Introductionmentioning
confidence: 99%